Vaping as a catalyst for smoking?: an initial model on the initiation of electronic cigarette use and the transition to tobacco smoking among adolescents - Schneider, Sven; Diehl, Katharina (Nicotine & tobacco research, 2016)
Introduction: The popularity of electronic cigarettes (e-cigarettes) among adolescents is growing worldwide. A more accurate model than the much discussed but inadequate Gateway Hypothesis is needed to explain some adolescents’ initial preference for e-cigarettes over tobacco cigarettes, as well as any transition from e-cigarettes to tobacco smoking. Our aim was to summarize the diffuse fear that adolescents will be indirectly encouraged to begin smoking tobacco via the use of e-cigarettes and to systematize the disparate causal hypotheses used thus far in relevant literature. Methods: We summarized the vague and fragmented hypotheses formulated thus far in literature on both trajectories from abstinence to e-cigarette use and from there to tobacco smoking into a set of empirically testable hypotheses and organized them into a comprehensive model. Results: Our results indicate that the perceived health risks, specific product characteristics (such as taste, price and inconspicuous use), and higher levels of acceptance among peers and others potentially make e-cigarettes initially more attractive to adolescents than tobacco cigarettes. Later, increasing familiarity with nicotine could lead to the reevaluation of both electronic and tobacco cigarettes and subsequently to a potential transition to tobacco smoking. The suggested “catalyst model” takes variations in the nicotine content of e-cigarettes as well as the dual use of different substances into account. Conclusion: Our model provides causal hypotheses for the initiation of e-cigarette use and for the potential transition to tobacco smoking which, after being tested in empirical studies, could lead to the formulation of concrete recommendations for healthcare intervention and prevention measures. Implications: We developed a model that provides causal hypotheses for the initiation of e-cigarette use and for the potential transition to tobacco smoking.
Gesehen am 17.05.2019
Advance Access publication September 18, 2015